2013
DOI: 10.4236/jcpt.2013.34020
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Growth, Crystal Structure and Characterization of the o-Toluidinium Picrate

Abstract: A new organic charge transfer molecular complex salt of o-toluidinium picrate (OTP) was synthesised and the single crystals were grown by the slow solvent evaporation solution growth technique using methanol as a solvent at room temperature. Formation of the new crystal has been confirmed by single crystal X-ray diffraction (XRD) and NMR spectroscopic techniques. The crystal structure determined by single crystal X-ray diffraction indicates that both the cation and the anion are interlinked to each other by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Protonation of the amino acid on the N1 site is reflected in the N1-C2-C3 and N1-C2-C1 angles which vary in the range 117.7 (2) and 121.8 (2) . This also occurs with other salts of toluidinium derivatives (Mohana Priyadarshini et al, 2013).…”
Section: Crystal Structuresmentioning
confidence: 74%
“…Protonation of the amino acid on the N1 site is reflected in the N1-C2-C3 and N1-C2-C1 angles which vary in the range 117.7 (2) and 121.8 (2) . This also occurs with other salts of toluidinium derivatives (Mohana Priyadarshini et al, 2013).…”
Section: Crystal Structuresmentioning
confidence: 74%
“…Mohana Priyadarshini et al [75,76] studied the synthesis, structure and characterization of m-toluidinium picrate and o-toluidinium picrate. It is reported that N-H•••O and C-H•••O are responsible for crystalline cohesion.…”
Section: The Molecules In the Crystal Are Linked By N-h•••o N-h••n An...mentioning
confidence: 99%
“…Light passing through any NLO material gets altered which depends on its temperature, orientation and wavelength of the light etc [5][6][7]. The organic materials with inclusion of aromatic ring are highly suitable for χ (2) (second-order) and χ (3) (third-order) NLO applications since their high optical damage, higher nonlinearity and ultrafast or electronic response [8]. There is a huge ultimatum, for novel NLO materials with large NLO figures of merit that are widely used as they possess good stability, large laser damage threshold with low mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…Mulliiken approach is based on the interactions of transfer of charge from the two aromatic molecules which arises out of electron transfer of complex of Lewis base to Lewis's acid. Generally, visible region's laser radiation gets absorbed when there is an interaction between e-(electron) donor and e-acceptor molecules which further leads to the origin of intensely colored charge transfer complexes [8,11]. Organic NLO crystals are too difficult to grow a large crystal than inorganic crystals because of weak intermolecular binding energy [12].…”
Section: Introductionmentioning
confidence: 99%